Effect of Role-Playing Strategy on the Development of Descriptive Skills for Cosmic Occurrences Among Grade 11 General Academic Strand Students in Las Piñas City National Senior High School – CAA Campus - Tura, Gerame (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2022)
study responded to the spiral path of Senior High School Science curricula, so the study chose the sample from the Grade 11 General Academic Strand Students in Las Piñas City National Senior High School – CAA Campus. The researcher divided the students into two different groups in content and roles. Moreover, the researcher allowed the students to exchange roles. Also, the researcher planed three consecutive class lessons for the concept of the solar eclipse, the lunar eclipse, and the solar system. After completing the stage of defining the research question and the general framework of the study steps, the principal agreed to the procedures to implement the research plan. Then, the researcher held a training session for teachers that included a brief presentation of the research objectives, tools, and procedures. Furthermore, the researcher took the voluntary official approvals to participate in the research from the study sample. Then the researcher began planning lessons, preparing educational resources, and assessment tools. The researcher determined the educational patterns of the learners by following them closely for three consecutive days and in cooperation with the directed teacher. In the implementation phase of the study, the researcher applied a blueprint for dramatic texts and distributed roles to students according to the plan. Then, the researcher distributed a written and visual guide to enable students to understand the phenomenon and simulate it. Students showed a simulation of the solar eclipse accompanied by a single worksheet that measures understanding and record learning descriptions. Following, the students introduced the lunar eclipse phenomenon, accompanied by another worksheet, and the student completed the learning progress record. Then the students wrote reflections on their learning experience. After completing the research investigation, the researcher interviewed the focus groups. Finally, the researcher tabulated all data and analyzed it to produce learning implications that explain and evaluate the impact of this strategy on learning.